Colored Biological Comic with Pictorial Mind Map on Material Human Circulation System to Increase Reading Interest of Junior High School Student - Adilah Yuan Nofista; Ristiono Ristiono (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2022)
The problem of this research is less interest of reading about human circulation system in Junior High School. Based on the observation, students has problem to understand tough topic. The purpose of this research is how to develop a colored biological comic with pictorial mind map and increase learning motivation about human circulation system for Junior High School. This research has been developed by using 3 stages of 4D models, that is define stage by defining the terms of learning using the curriculum, design stage by designing prototype of biological comic which designed with hybrid method using manual tools and Adobe Photoshop CS6, and develop stage that aims to produce a valid and practical biological comic with validity test by 3 validators and practicality test by 1 biology teacher and 25 student in VIII.A of Pembangunan Junior High School. The result of this research obtained by validity and practicality test to the comic. The average of validity value is 92.88% with very valid criteria. The average of practicality test by teacher is 95.14% with very practical criteria and by students is 88.40% with practical criteria. This research shows this biological comic result is categorized by very valid and practical to use by teachers and students in teaching and learning.